Code Switching and Code Mixing in Speech Act Between The Seller and The Buyer - Dede Rosyadi; zulkhaeriyah; Imran Trista Udin (Hasanuddin University, 2023)
In this study, there is an explanation of the factors that cause code switching and code mixing. To analyze the factors that cause code switching, researchers use Suwito's theory (in Rulyandi et al., 2014) which divides the factors that cause code switching into 6, namely factors from the speaker, interlocutor, third person, subject matter, evoking a sense of humor, and gensi. While the factors that cause code mixing use Suandi's theory (in Munandar, 2018) which divides the factors that cause code switching into 6, namely factors from speakers, interlocutors, third person, subject matter, evoking a sense of humor, and gensi. The occurrence of code mixing becomes 13, namely the limitations of code use, the use of more popular terms, the speaker and the speaker's personality, the speaking partner, the place of residence and the time when the conversation takes place, mode of conversation, topic, function and purpose, variety and level of speech, the presence of third speakers, subject matter, to generate a sense of humor, and for prestige. Based on the data obtained, there are five code-switching conversations that have four factors from the speakers contained in conversations 1-4 and one factor from presenting the third person found in conversation 5. In conversation 1-4, the causal factor of the speakers, code-switching is used because there is an interest to familiarize the speech partners and speakers who are natives who usually use their local language to communicate daily. While the causal factor in conversation 5, code switching is used because the speech partner repeats the speech of the third person. The factors causing code mixing in this study are found in conversations 6-11. In conversations 6, 9, and 11, code mixing occurs due to the limited use of code by speakers. So, the speaker does not know the equivalent word used so he mixes the code by combining Indonesian with Javanese and vice versa. Then in conversation 7, the factor that causes code mixing is the presence of a third person, so the speech partner presents a third person in the conversation and the third person combines Indonesian with Betawi. Then, in conversation 8, the factor that causes code mixing is the use of popular terms. This happens because it is the age of online business so, people know the terms used in online business. Furthermore, in conversation 10 there are factors that cause code mixing from the speaker and the speaker's personality. This happens because the speaker has the intention to change the conversation to a more relaxed situation. Based on the results of the above research, the most dominant factor causing code mixing is the limited use of code by speakers (Fitriyah, 2020; Ninsi & Rahim, 2020).